Increases in energy prices could have a stronger effect on consumer prices than decreases - Victoria Havsteen Branner (Danmarks Nationalbank, 2024)
Going forward, Europe risks more volatile energy prices due to geoeconomic fragmentation, climate change and the transition to renewable energy sources. This economic memo explores the pass-through from changes in energy prices to consumer prices in Denmark and the euro area. The results indicate that increases in the price of natural gas or crude oil have a greater effect on consumer prices than decreases. Awareness of this asymmetry is important for central banks in safeguarding price stability.
Keywords: 330